플립러닝 기반의 임상치위생학 교육과정 개발 및 적용 사례연구 - 정수라; Su-ra Jeong; 김미선; Mi-sun Kim; 김은정; Eun-jeong Kim; 최용금; Yong-keum Choi (Han'guk Ch'iwisaeng Hakhoe chi, 2020)
Objectives: The purpose of this study is to prove, through the design and operation of a teaching learning model for clinical dental hygiene and practice III, the effectiveness of the flipped learning PARTNER model. Methods: A professional council was formed, composed of three professors of dental hygiene and one professor of education; each member was an expert with a Ph.D. From December 2018 to February 2019. Results: Learning preferences for the clinical learning hygiene curriculum based on flip learning showed that it had higher accessibility than traditional teaching methods. Subjects’ motivation to learn was improved through flip learning, their critical thinking ability was improved through active discussion and flip team discussion, and their self-directed learning ability was also improved. Participation increased through flipped learning, and subjects’ skill abilities showed their highest score by improving their performance through the whole lecture. A high satisfaction of 4.54 out of 5 points was achieved. Conclusions: It was confirmed that the development and operation of a flipped learning-based clinical hygiene curriculum can provide an effective and satisfactory learning process.